2013
DOI: 10.1186/2110-5820-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Lactate clearance for death prediction in severe sepsis or septic shock patients during the first 24 hours in Intensive Care Unit: an observational study

Abstract: BackgroundThis study was design to investigate the prognostic value for death at day-28 of lactate course and lactate clearance during the first 24 hours in Intensive Care Unit (ICU), after initial resuscitation.MethodsProspective, observational study in one surgical ICU in a university hospital. Ninety-four patients hospitalized in the ICU for severe sepsis or septic shock were included. In this septic cohort, we measured blood lactate concentration at ICU admission (H0) and at H6, H12, and H24. Lactate clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
100
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(117 citation statements)
references
References 30 publications
9
100
1
7
Order By: Relevance
“…In non-survivors of sepsis, we observed a consumption coagulopathy state, characterized by decreased antithrombin and prothrombin levels, decreased platelet counts, prolonged PT and CAT lag time, all pointing towards an up-regulation of haemostatic processes and consumption of coagulation proteins. We confirm that nonsurvivors present with significantly increased CAT lag times and lactate/LDH levels and that septic shock patients have decreased platelet counts, as well as decreased prothrombin and antithrombin levels [25][26][27][28][29][30][31]. Likewise our data support the view that different functional methods of coagulation assessment may result in different outcomes when tested for this particular type of patients (cf.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In non-survivors of sepsis, we observed a consumption coagulopathy state, characterized by decreased antithrombin and prothrombin levels, decreased platelet counts, prolonged PT and CAT lag time, all pointing towards an up-regulation of haemostatic processes and consumption of coagulation proteins. We confirm that nonsurvivors present with significantly increased CAT lag times and lactate/LDH levels and that septic shock patients have decreased platelet counts, as well as decreased prothrombin and antithrombin levels [25][26][27][28][29][30][31]. Likewise our data support the view that different functional methods of coagulation assessment may result in different outcomes when tested for this particular type of patients (cf.…”
Section: Discussionsupporting
confidence: 89%
“…Other causes for increased lactate/LDH levels includes a decreased clearance of lactate by the liver [35,36]. Previous research [25,30,31] has shown that increased lactate levels or the failure to clear lactate or LDH within the first 24-48 hours after ICU admittance are strong predictors of mortality in sepsis patients, in agreement with the significantly increased lactate/LDH activity levels observed in non-survivors (P = 0.001), compared to survivors of sepsis in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression analysis showed that lactate clearance was associated with mortality in sepsis patients (OR 0.35; 95%CI 0.01 to 0.76; P=0.047). 18 In our study, low lactate clearance was significantly associated with greater risk of mortality A previous study used lactate clearance as a benchmark of the success of early goal-directed therapy (eGDT) in patients with sepsis. In the study, lactate clearance was a good indicator for assessing the success of the first 6 hours of eGDT in septic patients.…”
Section: Discussionmentioning
confidence: 83%
“…For septic patients in the ICU, a lactate clearance-directed therapy in the first 6 hours appeared as efficient as ScvO2 measurement. 15 However no data are availabe for lactate-directed therapy for longer duration, nor on blunt abdominal trauma settings in the emergency room.…”
Section: Discussionmentioning
confidence: 99%